Brood Production by Xyleborus glabratus in Bolts from Trees Infected and Uninfected with the Laurel Wilt Pathogen, Raffaelea lauricola. Issue 6 (14th June 2018) - Fraedrich, Stephen W; Harrington, Thomas C; Huang, Qiong; Zarnoch, Stanley J; Hanula, James L; Best, Glenda Susan
Abstract: Raffaelea lauricola is the causal agent of laurel wilt and a fungal symbiont of its vector, the redbay ambrosia beetle, Xyleborus glabratus . Beetle populations increase rapidly where redbays have died from laurel wilt. In a series of experiments using bolts from healthy and diseased trees, X. glabratus reproduced better in bolts from diseased redbay; ratio of beetles emerged to entrance holes (BE/EH ratio) ranged from 4.1 to 6.0 in diseased bolts versus 0.3 to 1.9 in healthy bolts. Emergence was greater from redbay bolts when their ends were treated with paraffin wax compared to untreated bolts. Although sassafras sapwood has been considered poor brood material for X. glabratus, bolts from a diseased sassafras had BE/EH ratios comparable to those from diseased redbay bolts. It was hypothesized that better brood production in bolts from diseased trees was due to precolonization of the bolts by R. lauricola, which would allow for better establishment of the pathogen in beetle tunnels. However, the frequency of R. lauricola isolation and colony forming units (CFU) per beetle did not differ between beetles emerged from diseased versus healthy redbay bolts. Changes in the xylem of trees with laurel wilt appear to provide conditions favorable for brood production.